Neurochemical effects of long-term hypoxia on noradrenergic neurons in nucleus tractus solitarius of the rat - Pequignot, Jean-Marc; Denavit-Saubié, Monique (Acta Andina, 2025)
In order to determine the effects of long-term hypoxia on catecholamine activity in the nucleus tractus solitarius (NTS), male rats were subjected to normobaric hypoxia (10% O2 in nitrogen) lasting for 3 days, 1, 2 or 3 weeks. Ventilation increased gradually during the hypoxic exposure before reaching a plateau after 10 days of hypoxia. Long-term hypoxia stimulated the norepinephrine turnover in noradrenergic neurons located in the NTS caudal to the obex, the discrete region to which the chemosensory carotid afferents project. Bilateral chemodenervation abolished the central changes in noradrenergic activity. The activity and quantity of tyrosine hydroxylase (TH), the rate-limiting enzyme of catecholamine biosynthesis, and the level of mRNA coding for TH were increased in the caudal NTS in response to long-term hypoxia, indicating induction of new molecules of TH protein. These neurochemical changes occurred after long-term hypoxia only, suggesting that noradrenergic neurons are involved in the central chemoreceptor pathway during sustained hypoxia but are not essential for regulatory responses to acute hypoxia. Norepinephrine released under long-term hypoxia could play a neuromodulatory role in ventilatory acclimatization.